PERBANDINGAN REVERSE BARBEAU TEST (RBT) DAN PENILAIAN KLINIS PADA PATENSI ARTERI RADIALIS PASCA KATETERISASI JANTUNG - Karina Sukmaningtyas; Arimbi Karunia Estri; Ignatius Gonggo Prihatmono (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2026)
Transradial cardiac catheterization is increasingly preferred due to its safety and patient comfort; however, radial artery occlusion (RAO) remains a concern as it may limit future radial access. The Reverse Barbeau Test (RBT) has been recommended as an objective method to assess radial artery patency, although clinical assessment is still commonly applied in the ICU of Panti Rapih Hospital. This study aimed to compare the Reverse Barbeau Test and clinical assessment in evaluating radial artery patency among post–cardiac catheterization patients. A comparative study design was conducted using accidental sampling involving 35 post-catheterization patients with radial compression devices admitted to the ICU of Panti Rapih Hospital, Yogyakarta. The study was conducted from May 23 to June 17, 2025. Data were analyzed using the McNemar test. The results showed a statistically significant difference between RBT and clinical assessment at 15 minutes after radial compression application (p = 0.001). RBT was more sensitive in detecting early impairment of radial artery patency, identifying 34.3% of cases compared to only 2.9% detected by clinical assessment. These findings indicate that the Reverse Barbeau Test is more sensitive for early detection of radial artery patency disturbances. Reverse Barbeau Test is objective, non-invasive, easy to perform, and cost-effective; therefore, its use is recommended, particularly during the first 15 minutes following radial compression device application.